2023
DOI: 10.3390/pharmaceutics15030881
|View full text |Cite
|
Sign up to set email alerts
|

Combined Dopamine and Grape Seed Extract-Loaded Solid Lipid Nanoparticles: Nasal Mucosa Permeation, and Uptake by Olfactory Ensheathing Cells and Neuronal SH-SY5Y Cells

Abstract: We have already formulated solid lipid nanoparticles (SLNs) in which the combination of the neurotransmitter dopamine (DA) and the antioxidant grape-seed-derived proanthocyanidins (grape seed extract, GSE) was supposed to be favorable for Parkinson’s disease (PD) treatment. In fact, GSE supply would reduce the PD-related oxidative stress in a synergic effect with DA. Herein, two different methods of DA/GSE loading were studied, namely, coadministration in the aqueous phase of DA and GSE, and the other approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Indeed, it can be observed that, only for DA-co-GSE-SLNs-Me-β-CD and GSE-ads-DA-SLNs-sucrose systems, a C1s deconvolution was typical of the carbohydrate-based systems, thus evidencing a surface presence of sucrose (or Me-β-CD). In all the other systems, C1s curve-fitting was typical of plain SLNs (whose curve-fitting has already been reported by us [12]), thus evidencing a negligible presence of the cryoprotectant on the surface. Similar C1s curve-fittings were observed for the non-cryoprotected systems reported in Figure S1 (see Supplementary Data).…”
Section: X-ray Photoelectron Spectroscopy Analysis (Xps)supporting
confidence: 77%
See 2 more Smart Citations
“…Indeed, it can be observed that, only for DA-co-GSE-SLNs-Me-β-CD and GSE-ads-DA-SLNs-sucrose systems, a C1s deconvolution was typical of the carbohydrate-based systems, thus evidencing a surface presence of sucrose (or Me-β-CD). In all the other systems, C1s curve-fitting was typical of plain SLNs (whose curve-fitting has already been reported by us [12]), thus evidencing a negligible presence of the cryoprotectant on the surface. Similar C1s curve-fittings were observed for the non-cryoprotected systems reported in Figure S1 (see Supplementary Data).…”
Section: X-ray Photoelectron Spectroscopy Analysis (Xps)supporting
confidence: 77%
“…Throughout the manuscript, the resulting SLNs were abbreviated "DA-co-GSE-SLNs". For GSE-adsorbing DA SLNs, DAloaded SLNs were first formulated as reported elsewhere [10,12] but starting from 20 mg of DA rather than 10 mg to force neurotransmitter initial cargo. After cooling the particles down at room temperature, an aliquot of 0.5 mL of the resulting DA-SLNs was incubated with 1 mL of GSE aqueous solution (1 mg/mL concentration) at room temperature for 3 h under light protection and maintaining mild stirring (50 oscillations/min).…”
Section: Solid Lipid Nanoparticle Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we focused on the in vitro effects of DA/GSE-SLN administration by exploiting the advantage of differentiated SH-SY5Y cells both as promising models for developing therapies for PD and for testing SLNs [38][39][40]; the same study was previously conducted on undifferentiated SH-SY5Y cells [32]. The SLNs tested here are highly performing transport systems exploited by the pharmaceutical research for their ability to efficiently cross the BBB when the particle size is in the range of 200-500 nm, so they have an increased blood circulation time and the drug is in contact with the BBB for the maximum time.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a project aiming at brain delivery of new lipid nanocarriers by intranasal administration, we prepared two different types of in vitro formulations of SLNs combining the neurotransmitter DA and the natural antioxidant mixture Grape Seed Extract (GSE). We formulated SLNs in which both active principles were co-loaded with SLNs in which GSE was physically adsorbed onto preformed DA-SLNs [31,32], according to the working hypothesis that an antioxidant-based therapy might reduce ROS connected to PD along with providing a synergistic effect with the exogenous DA supply. Indeed, rather than exploiting the antioxidant effects arising from vitamin E [33,34], we selected polyphenols from GSE, mainly consisting of proanthocyanidins, to assess both their potential therapeutic and antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%